Motivation of student radiographers in learning situations based on role-play simulation: A multicentric approach involving trainers and students. Issue 1 (February 2019) - Zorn, C.; Dillenseger, J.-P.; Bauer, E.; Moerschel, E.; Bachmann, B.; Buissink, C.; Jamault, B.
Abstract: Introduction: Role-play simulation is implemented in different radiography institutions. This tool develops Knowledge, Skills and Competences (KSC) in students. The aim of this study was to identify the strategies implemented by trainers in order to encourage student motivational dynamics and to find those that resonate with students. Methods: Three role-play simulation sessions using a grid were observed in two different radiography institutions that have a simulation centre (two French institutions and one Swiss). In order to identify explicitly or implicitly the motivational strategies used, four interviews with trainers were conducted. To understand students' opinions about these strategies, seven interviews with radiography students were done. Results: Defining motivation was not easy. The trainers used various strategies to motivate students, not all of which were verbalized in interviews. Although students said they were stressed prior to participating in role-play simulation, this study shows that such simulation sessions are effective to develop high motivational dynamics for students. Conclusion: This study has identified three main areas of improvement: exploring students' expectations, give importance to patients briefing so that they can fully perform their role and improving the authenticity of the environment. The latter issue can only be addressed through access to up-to-date equipment in training institutions. Highlights: Simulation has a positive impact on the motivational dynamics of student radiographers. In simulation, trainers implement various strategies to motivate students. To raise students' motivational level, teachers should explore their expectations in advance. Teachers must ensure the authenticity of the environment.